2021
DOI: 10.1007/s11926-021-01015-9
|View full text |Cite
|
Sign up to set email alerts
|

The Nasal Microbiome in ANCA-Associated Vasculitis: Picking the Nose for Clues on Disease Pathogenesis

Abstract: Purpose of Review The onset and progression of small vessel vasculitis associated with anti-neutrophil cytoplasmic antibodies has been linked to microbial infections. Here, we provide a brief overview of the association of nasal colonization of Staphylococcus aureus with ANCA-associated vasculitis (AAV) and discuss several recent studies mapping the nasal microbiome in AAV patients in particular. Recent Findings Nasal microbiome studies revealed dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Nasal microbiome studies have revealed dysbiosis as a common trait in active AAV, which tends to normalize upon immunosuppressive treatment and in quiescent disease. However, the reported microbiome profiles differ considerably among patients [70]. Many studies have focused on S. aureus, with reports of increased rates of nasal carriage in patients with GPA and frequent relapses [71].…”
Section: The Role Of Infections and Microbiomementioning
confidence: 99%
“…Nasal microbiome studies have revealed dysbiosis as a common trait in active AAV, which tends to normalize upon immunosuppressive treatment and in quiescent disease. However, the reported microbiome profiles differ considerably among patients [70]. Many studies have focused on S. aureus, with reports of increased rates of nasal carriage in patients with GPA and frequent relapses [71].…”
Section: The Role Of Infections and Microbiomementioning
confidence: 99%
“…A publication demonstrated the contribution of TLR9 polymorphisms to PR3-AAV susceptibility and clinical presentation [34]. While Staphylococcus aureus (S. aureus) was believed to be a potential trigger for AAV traditionally [126,127], recent publications show that these studies were flawed and do not accurately represent a solid association between S. aureus infection and disease pathogenesis [128,129]. Perhaps a dysfunctional response to infection may be the determinant of AAV susceptibility.…”
Section: Non-hla Region Snpsmentioning
confidence: 99%
“…Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis represents a cluster of small-vessel vasculitis including microscopic polyangiitis (MPA), granulomatosis with polyangiitis (GPA), and eosinophilic granulomatosis with polyangiitis (EGPA), which are all associated with ANCA, mainly causing arteriole damage and having a similar renal histology (e.g., focal necrotizing pauci-immune crescentic glomerulonephritis). Because ANCA-associated vasculitis (AAV) is characterized by mucosal inflammation including upper and lower respiratory tract inflammation, most studies have focused on nasal microbiome; one such review has been conducted by Dekkema et al (2021), which reviewed nasal microbiome studies on AAV and concluded that nasal dysbiosis is a common phenomenon in active AAV, and immunosuppressant treatment can ameliorate nasal microbiome disorder. However, because of different study designs and population selection, the reported results of nasal microbiome differed between studies.…”
Section: Anca-associated Vasculitismentioning
confidence: 99%
“…However, because of different study designs and population selection, the reported results of nasal microbiome differed between studies. Accordingly, it is hard to determine a causal relationship between nasal dysbiosis and AAV ( Dekkema et al., 2021 ).…”
Section: Small-vessel Vasculitismentioning
confidence: 99%